MENTAL DEFICIENCY - TO FIND A PERSON A SUBJECT OF CRIME AS A HINDERING CONDITION - Abdurasulova Kumrinisa (International Journal of Business, Law and Political Science, 2025)
Objective: This study aims to explore the role of forensic psychiatric examinations in determining the mental state of individuals accused of crimes. It seeks to clarify the relationship between mental disorders and criminal liability, focusing on how both medical and legal criteria are used to assess an individual's sanity. By examining the application of these criteria in judicial processes, the study highlights the importance of ensuring that criminal liability is assigned based on an individual's ability to understand and control their actions. Method: The research employs a comprehensive analysis of forensic psychiatric assessments, incorporating case studies, legal provisions (specifically Article 18 of the Criminal Code of Uzbekistan), and expert opinions. This method systematically evaluates the relationship between mental health conditions and criminal accountability, integrating clinical diagnoses with legal standards to provide a nuanced understanding of sanity in the context of criminal law. Results: The study finds that forensic psychiatric evaluations are essential in determining sanity, defined as the ability to understand the nature of one's actions and control one's behavior. Mental disorders, such as schizophrenia or temporary conditions like alcoholic psychosis, affect legal judgments. The dual-criteria approach—cognitive and volitional—ensures comprehensive assessments, considering both the individual's mental condition and their legal responsibility at the time of the offense. Novelty: This research introduces a dual-criteria framework, combining medical diagnoses and legal definitions of criminal liability. It emphasizes the importance of forensic psychiatric evaluations in ensuring fair criminal responsibility assignments, recognizing the complexities of mental health within the legal system.